Deferred Prosecution Agreement: a Restorative Approach in Tackling Corruption Committed by Corporations - Mas Putra Zenno Januarsyah; Widiada Gunakaya; Asep N. Mulyana (Sekolah Tinggi Hukum Bandung, 2022)
This study aims to analyze the restorative approach to overcoming criminal acts of corruption committed by corporations through a deferred prosecution agreement. This research is descriptive with normative juridical research using secondary data in the form of primary, secondary, and tertiary legal materials through a statute approach and a conceptual approach. Data was collected using a document study, then analyzed qualitatively. The study results show that the deferred prosecution agreement is the ideal model for returning state financial losses due to corruption. This concept can be applied in Indonesia. In addition, this model provides legal certainty and legal benefits. As a consequence, as a dual-track system, deferred prosecution agreements also remain in the corridor of settlement through the criminal justice system.